The effectiveness of Entrepreneurship Education on entrepreneurial Interest and the ability of Sharia-based entrepreneurship - Badriyah, Hasna; Kurniawan, Muhammad; Susanto, Is (Indonesian Journal of Islamic Economics and Finance, 2025)
One of the key factors influencing an economy's development is entrepreneurship. Students are supposed to gain knowledge and refine their entrepreneurship abilities at universities. The purpose of this study is to ascertain whether the state Islamic University of Raden Intan Lampung's entrepreneurship curriculum is successful in producing new Sharia entrepreneurs. A sample of 61 Bachelor S1 students enrolled in the Sharia Business Management Study program at UIN Raden Intan Lampung participated in this quantitative research study. SEM analysis utilising intelligent PLS software is the data analysis method employed in this investigation. Probability sampling is the sampling technique employed in this investigation. The study's findings suggest that UIN Raden Intan Lampung's entrepreneurship education is effective since it significantly and favourably influences students' interest in and capacity for sharia-based entrepreneurship at S1 UIN Raden Intan Lampung with Sharia Business Management Study program. The findings of this study are consistent with Ajzen and Fishbein's (1985) Theory of Planned Behaviour, which holds that training and education pertaining to entrepreneurship can be considered effective if there is a positive correlation between the development of intentions and an increase in ability and success in entrepreneurship. The focus on Sharia features or Islamic economic principles in entrepreneurship, which influence people's interest and aptitude for entrepreneurship, is where this study differs from earlier research.